The Living Force: An Ecological Reading of How the Force Regards Its Adherents - Gormley, Michael J. (Journal of religion and popular culture, 2019)
Drawing on the new canon, this article explores the ecological nature of the Force to evaluate the abilities and actions of its most visible adherents, the Jedi and the Sith. Through particular attention to prophecy and animal taming, this article demonstrates that the near extinction of the monastic Jedi resulted from a failure to adhere to the will of the Force, which then empowered the predatory Sith to cull the Jedi and balance the environment. Close readings of Coruscant, Dagobah, and other planets offer insight into the Force's nature, which clarifies Palpatine's deposal of the Jedi while corrupting Anakin Skywalker, unpacks Yoda's exile, illuminates technological relics manifested by the living Force, and explicates the final duel of Episode VII: The Force Awakens.